Fecundity rate and pregnancy outcome after surgical treatment of ectopic pregnancy in Hospital Kuala Lumpur - Husin, Azilah (2015)
Introduction: Ectopic pregnancy is a gynaecological emergency and is an important cause of morbidity and mortality in developing countries. Although the risk factors of ectopic pregnancy have been determined in previous studies, the main risk factors of ectopic pregnancy are different in various countries due to different cultural and social characteristics. Early diagnosis and referral may reduced the morbidity and mortality associated with this life threatening condition. With earlier diagnosis, medical therapy with methotrexate can be offered and surgical management may be avoided. However, this will need a protocol for patient follow up for medical or expectant management of ectopic pregnancy. In the surgical management of ectopic pregnancy, the benefits of salphingectomy over salphingostomy in predicting the future fertility are uncertained. Laparoscopy procedure is generally more favored over laparotomy. However, it depends on the stability of the patient's haemodynamic status. However, whether thesesurgical factors and surgeon's expertise will affect the subsequent pregnancy and its outcome is questionable. Objectives: To determine the fertility rate and pregnancy outcome after ectopic pregnancy that has been managed surgically in Hospital Kuala Lumpur. Patients and Methods: A retrospective study was carried out in the Department of Obstetrics and Gynaecology in Hospital Kuala Lumpur, utilizing the data from the year 2006 to 2010. This comprised of randomly 120 patients that presented for ectopic pregnancy managed surgically and also confirmed histology. The surgical approach and the level of surgeon data were determined from patient's case notes and analyzed for the associations and significance. Statistical significance was taken as p value of less than 0.05 (p<0.05). Results: From 120 patients of ectopic pregnancy during the study period, 41 patients were able to conceive within 5 years after the ectopic pregnancy. Out of this subsequent pregnancy, there were 29(70.7%) intrauterine pregnancies and 12(29.3%) recurrent ectopic pregnancies. Out of the intrauterine pregnancies, 24(82.8%) had live birth babies and another 5(17.2%) had miscarriages. The mean time to next pregnancyfor patient to get pregnant was 18.73±11.267 months. The maternal characteristics (age, parity and smoking status) do not contributed to the risk of recurrent ectopic pregnancy. The surgical approach and the surgeon's level also do not have any statistically significant for the fecundity rate and the subsequent pregnancy outcome. XVConclusion: In view that any surgical approach and type of surgery done for the ectopic pregnancy does not influence the fecundity rate in subsequent pregnancy, the choice for surgical management in a stable patient should be the one that has less surgical complications, therefore laparoscopy procedure should be encouraged.